Understanding Marketing Environment in Indian Context: Exploring the impact of internal and external forces on successful customer relationships in the Indian marketing environment (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The marketing environment represents a mix between the internal and external forces which surround an organization and have an impact upon it, especially their ability to build and maintain successful relationships with target customers. The marketing environment represents a mix between the internal and external forces which surround an organization and have an impact upon it, especially their ability to build and maintain successful relationships with target customers.